2013
DOI: 10.1038/modpathol.2012.196
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic analysis of IgG4-related skin disease

Abstract: IgG4-related disease is a recently recognized systemic syndrome characterized by mass-forming lesions with lymphoplasmacytic infiltration, increase in the number of IgG4 þ cells in affected tissues and elevation of serum IgG4 levels. In 2009, we were the first to report skin lesions in patients with IgG4-related disease, but no large case series has been reported and clinicopathological findings remain unclear. To clarify these features, we herein report 10 patients (9 men and 1 woman; median age, 64 years; ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(128 citation statements)
references
References 10 publications
(28 reference statements)
5
118
2
3
Order By: Relevance
“…[24][25][26][27][28][29] In the largest and bestcharacterized published series of 10 patients with IgG4-related skin disease, 24 8/10 patients were 450 years old, in 8/10 patients extracutaneous manifestations of IgG4-related disease could be proven (lymph node, lacrimal and/or salivary gland, and kidney), and all 10 patients showed an elevated serum IgG4 level. Regarding the localization of IgG4-related skin disease that generally present on the head and neck, particularly cheek, periauricular, and mandible regions, our cases of IgG4 þ primary cutaneous marginal zone lymphomas in contrast showed preferential manifestations on the back, shoulders, and upper extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29] In the largest and bestcharacterized published series of 10 patients with IgG4-related skin disease, 24 8/10 patients were 450 years old, in 8/10 patients extracutaneous manifestations of IgG4-related disease could be proven (lymph node, lacrimal and/or salivary gland, and kidney), and all 10 patients showed an elevated serum IgG4 level. Regarding the localization of IgG4-related skin disease that generally present on the head and neck, particularly cheek, periauricular, and mandible regions, our cases of IgG4 þ primary cutaneous marginal zone lymphomas in contrast showed preferential manifestations on the back, shoulders, and upper extremities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, typical histopathological characteristics of IgG4-related disease, such as fibrosclerosis, obliterative phlebitis, or an increased Although IgG4-related disease is a polyclonal disease, IgG4 þ primary cutaneous marginal zone lymphomas are clonal proliferations with light chain restriction. Clonality and/or light chain restriction have not been detected so far in four recent publications [24][25][26]30 dealing with IgG4-related skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…22 The largest study of patients with IgG4-related skin disease to date (n = 10) reported an IgG4+ plasma cell density of 49 to 396 cells per hpf, with an IgG4/IgG ratio of 0.62 to 0.92. 14 Another study of five patients with cutaneous manifestations of IgG4-RD reported an IgG4+ density of 23 to 128.6 per hpf. 15 Our data indicate that moderately elevated IgG4+ plasma cell density and IgG4/IgG ratio are not specific to IgG4-RD.…”
Section: Resultsmentioning
confidence: 99%
“…1,6,[8][9][10][11][12] Although cutaneous manifestations of IgG4-RD appear to be rare, they may produce nonspecific erythematous papules, nodules, and plaques. [13][14][15][16][17] Therefore, it would follow that evidence for IgG4-RD in the skin (an organ readily accessible for biopsy) may be of diagnostic utility, particularly in patients with nondiagnostic biopsy specimens from visceral organs. Investigators have defined cutoff values for IgG4+ tissue densities for the diagnosis of IgG4-RD for extracutaneous organs, 18 and a recent pathology consensus statement recommended that the IgG4 density for skin should exceed 200 cells per hpf 6 on the basis of anecdotal evidence.…”
mentioning
confidence: 99%
“…[1][2][3][4] Histological examination of IgG4-related disease has shown diffuse lymphoplasmacytic infiltration, interstitial fibrosis, obliterative phlebitis, and eosinophilic infiltration. Additionally, numerous IgG4-positive plasma cells are observed and the IgG4-positive/IgG-positive cell ratio is elevated above 40% in affected tissues.…”
mentioning
confidence: 99%